2021
DOI: 10.1259/bjr.20210340
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of qualitative and radiomics approach to parotid gland tumors: which is the added benefit of texture analysis?

Abstract: Objective: To investigate whether MRI-based texture analysis improves diagnostic performance for the diagnosis of parotid gland tumors compared to conventional radiological approach. Methods: Patients with parotid gland tumors who underwent salivary glands MRI between 2008 and 2019 were retrospectively selected. MRI analysis included a qualitative assessment by two radiologists (one of which subspecialized on head and neck imaging), and texture analysis on various sequences. Diagnostic performances including s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…It can also contribute to predict the prognosis in some instances [15][16][17]. Several recent articles have explored the value of radiomics, clinical, and their combined models for the classification of PA, WT, and malignancy [18][19][20][21][22]. However, the selection of clinical factors is not uniform.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can also contribute to predict the prognosis in some instances [15][16][17]. Several recent articles have explored the value of radiomics, clinical, and their combined models for the classification of PA, WT, and malignancy [18][19][20][21][22]. However, the selection of clinical factors is not uniform.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with T1-weighted images (T1WIs), T2WIs can provide more details about the internal structure of the tumor [23][24][25]. Furthermore, the T2WI-based radiomics model has the best diagnostic performance to differentiate WT from PA [22].…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics is an emerging method that could improve diagnostic accuracy through the quantitative analysis of data from images, and offers advantages over conventional biopsy including noninvasiveness, virtually unlimited repeatability, and possibility to assess the whole tumor tissue and to perform longitudinal follow-up testing [25] , [26] , [27] , [28] . While several articles have been published trying to differentiate benign from malignant salivary gland tumors based on radiomics features extracted from head-and-neck MRI examinations, there is still no consensus on which image sequences should be analyzed, with some studies using T2w images [11] and other ones DWI [15] or a combination of sequences (such as post-contrast T1w, T2w, DCE or apparent diffusion coefficient [ADC] images) [13] , [14] , [17] , [29] . In our study we selected to analyze T2w and pcfsT1w images, because these sequences are an essential part of MRI examinations aimed to the evaluation of a parotid mass, providing key information for the differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Fruehwald-Pallamar et al [13] and Sarioglu et al [12] found that texture analysis features derived from pcfsT1w images provided the most significant textural information in the discrimination between PA and WT. Conversely, Vernuccio et al [29] demonstrated that an MRI-based predictive radiomics model based on texture analysis of T2w images improved the diagnostic performance of non-subspecialized radiologists for the differential diagnosis between PA and WT. Our findings revealed that texture features obtained from T2w and pcfsT1w images can have good discriminatory performance, with skewness derived from T2-weighted images yielding highest specificity.…”
Section: Discussionmentioning
confidence: 99%
“…ADC-based texture analysis, as a non-invasive and quantitative additional supporting tool, can extract features of entire tumors and go beyond individual-based visual assessment ( 34 ). Previously, many studies ( 26 , 34 42 ) have explored the computer-assisted discrimination of benign and malignant parotid gland tumors, but only a few studies have evaluated the role of ADC-based radiomics features in the differentiation of parotid lesions ( 29 , 31 , 34 ). In our study, the ADC-based radiomics features were from three different manufacturers, which still shows a good performance in differentiating PA and WT from MTs.…”
Section: Discussionmentioning
confidence: 99%